DESIGN AND BUILD POS WEBSITE SOFTWARE FOR CV DIGITAL PRINTING BASED ON VISUAL CODE SOFTWARE USING THE IGNITER CODE FRAMEWORK 3 - Popon Handayani,; Ade Setiawan,; Santoso Setiawan, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study designs a web-based Point of Sale (POS) system for CV Digital Printing, focusing on requirements analysis, user-level page allocation, database design, software architecture, and associated costs. The primary goal is to streamline and expedite sales transactions, product stock management, sales reporting, and customer data management. The main page is divided into "Administrator" and "Cashier" sections, each featuring login functionality, sales transactions, and reporting. The database design is illustrated through an Entity Relationship Diagram (ERD). The software architecture employs an object-oriented approach (OOP) using the PHP programming language and open-source software. Cost details encompass hardware, such as VPS and DNS, as well as software expenses, including IDE and software licenses. Testing is conducted using the black-box method to ensure software quality and functionality alignment. This article discusses the crucial steps in designing a POS system tailored to the needs of CV Digital Printing.